2012
DOI: 10.15560/8.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Mammals of medium and large size in a fragmented cerrado landscape in northeastern Minas Gerais state, Brazil

Abstract: The diversity of Brazilian mammals is among the highest of the world. However this exceptional diversity is still widely unknown and great part of it is seriously threatened by human activities. In the present study we estimated species richness and relative abundance of medium and large size mammals for the region of Brasilândia de Minas, a city situated in a fragmented and poorly studied cerrado area of Minas Gerais state, Brazil. We obtained 63 records of 24 species, including eight species threatened with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
2
9
0
8
Order By: Relevance
“…This study obtained similar results to others studies conducted in "Cerrado" areas (BOCCHIGLIERI et al, 2010;LESSA et al, 2012). According to Silveira (2010), some animals may exhibit seasonal records throughout the year and specific registers in large time intervals, the duration of a year or more, which may allow short records or absence of such a study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study obtained similar results to others studies conducted in "Cerrado" areas (BOCCHIGLIERI et al, 2010;LESSA et al, 2012). According to Silveira (2010), some animals may exhibit seasonal records throughout the year and specific registers in large time intervals, the duration of a year or more, which may allow short records or absence of such a study.…”
Section: Discussionsupporting
confidence: 90%
“…The remnants of native vegetation, development of appropriate management plans, development of actions for the recovery of degraded areas and surveying are essential for the mammals' conservation (ANTUNES; ESTON, 2009;ROCHA;ALVES et al, 2012). Preserved areas of native vegetation and adjacent corridors directly contribute to the maintenance of mammalian diversity, and make sustainable environment for existing populations of wild mammals in one place HENRIQUES, 2009;DANTAS;DONATO, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The crab-eating fox (Cerdocyon thous) was also frequently recorded in other studies (Prado et al 2008;Dotta and Verdade 2011;Lessa et al 2012), which may be related to its tolerance to modified environments (Ferraz et al 2010) with an opportunistic and generalist diet . The black-horned capuchin (Sapajus nigritus) shows great diet flexibility and tolerance to small-sized and modified forest remnants (Auricchio 1995).…”
Section: Resultsmentioning
confidence: 65%
“…We did not record Dasyprocta sp., Nasua nasua or Lontra longicaudis, which are usually found in Atlantic Forest remnants (Modesto et al 2008;Dotta and Verdade 2011;Penido and Zanzini 2012). Nor did we record Chrysocyon brachyurus or Conepatus semistriatus, which are common species in Cerrado remnants (Rocha and Dalponte 2006;Lessa et al 2012). Rodrigues (2009) reported the occurrence of C. brachyurus and L. longicaudis in "Mata da Meia Lua", a forest remnant adjacent to AIEMC (8 km in a straight line).…”
Section: Resultsmentioning
confidence: 74%
“…found in the Formosa MTA represents approximately 62% of the medium-and large-sized species recorded in all the Cerrado range (Marinho-Filho et al, 2002;Paglia et al, 2012) and is higher than the richness found in the three other protected areas located in the Federal District combined (N ¼ 24; Juarez, 2008). Other studies carried out in the Cerrado reported species richness between 15 and 29 species (Alves, 2014;Bocchiglieri, Mendonc¸a, & Henriques, 2010;Bruna et al, 2010;Rocha & Dalponte, 2006;Rodrigues et al, 2002;Lessa, Alves, Lena, & Barreto, 2012;Moreira et al, 2008;Ribeiro & Melo, 2013). However, the species accumulation curve does not show an asymptotic tendency, indicating that the species richness in the Formosa MTA should be even higher.…”
Section: Discussionmentioning
confidence: 91%